DERIVATION AND SYNTACTIC FUNCTION TO DEAL WITH IELTS TEST A MORPHOSYNTACTIC APPROACH - Komang Astiari; I Wayan Budiarta (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2026)
This research analyzed how the study of derivational morphemes could help students who take IELTS test to deal with listening questions. The data was taken from Cambridge books which shows a wide range of derivation that paraphrase the sentence in the questions; thus, test-takers could easily identify the answer in the audio. The theory was proposed by Andrew Carstairs-McCarthy in his book entitled “An introduction to English Morphology: Words and Their Structure” and Noel Burton Roberts in his book Analyzing Sentences; An Introduction to English Syntax. The method used was qualitative method whereas all data was analyzed using description and syntactic tree. The study found that there were some changes in lexical categories namely noun to verb, verb to noun, verb to adjective, adjective to verb, verb to adverb, and adverb to verb. Those changes of lexical categories resulted in the changes of syntactic structure in the sentences which could be helpful for the test-takers in dealing with the listening section.